Factors Determining the Macroeconomic Impact of the Fiscal Policy: Theoretical Analysis - Velichkov, Nikolay; Stefanova, Kristina (Research Papers, 2019)
This paper studies and interprets the impact of the fiscal policy on the real economy within the framework of various theoretical concepts that allow for different strength of that impact. This strength depends on the power and the scope of the factors that can limit the fiscal policy macroeconomic effects. In this respect, the aim of the paper is to analyze the role of these factors in the actual manifestation of the interaction between fiscal policy and macroeconomic activity.
Keywords: Crowding out effect; Fiscal sustainability; Fiscal policy